Pengaruh Financial Literacy, Financial Attitude, dan Financial Self-Efficacy Terhadap Saving Behavior Pengguna Paylater - Jessyca Noviolita Putri; Sari Andayani (Al-Buhuts, 2024)
The purpose of this study is to prove the influence of financial literacy, financial attitude, and financial self-efficacy on saving behavior. The data used are primary data obtained directly from 98 respondents who are undergraduate accounting students at a public university in Surabaya. The sampling method used is non-probability sampling with a purposive sampling technique. Questionnaires filled out by the respondents were analyzed using quantitative analysis methods and smartPLS as the analytical tool. The results of this study indicate that financial literacy has a positive and significant effect on saving behavior, financial attitude has a positive and significant effect on saving behavior, and financial self-efficacy has a positive but not significant effect on saving behavior.